Endocrown restorations in premolars: influence of remaining axial walls of tooth structure and restorative materials on fatigue resistance - Demachkia, Amir Mohidin [UNESP]; Velho, Helder Callegaro; Valandro, Luiz Felipe; Dimashkieh, Mohiddin Rida; Samran, Abdulaziz; Tribst, João Paulo Mendes; de Melo, Renata Marques [UNESP] (Springer Nature, 2023)
Objectives: To evaluate the effect of the remaining tooth structure and different CAD/CAM materials on the fatigue performance and failure mode of endodontically treated premolars restored with endocrowns. Materials and methods: Ninety maxillary premolars were endodontically treated and assigned into 6 groups (n = 15) according to the number of remaining axial walls (four, three, and two) and restorative materials (ultra-translucent zirconia 5Y-PSZ [KATANA UTML] and lithium disilicate [IPS e.max-CAD]). The specimens were subjected to cyclic fatigue loading test (initial load 200 N; 20 Hz). An incremental step load of 100 N per 10,000 cycles was applied until failure. The fatigue failure load (FFL) and number of failure cycles (CFFs) data were statistically analyzed with two-way ANOVA and Kaplan–Meier test (α = 0.05). Failed specimens were examined under a stereomicroscope 25 × and failure modes were determined. Results: FFL and CFF were significantly influenced by restorative material (p < 0.05). 5Y-PSZ endocrowns showed significantly higher FFL when compared with lithium disilicate. The number of remaining walls did not affect the fatigue behavior or failure mode of the specimens. Of the lithium disilicate restorations, 51% had repairable failures, while 95% 5Y-PSZ restorations had non-repairable failures. Conclusions: Zirconia endocrowns showed better FFL than lithium disilicate endocrowns, regardless of the number of remaining axis walls. Lithium disilicate and 5Y-PSZ endocrowns showed FFL higher than the normal masticatory loads. Clinical relevance: Restoring endodontically treated premolars with endocrown could be a promising treatment, regardless of the remaining axial walls. However, precaution should be taken in material selection since it affects the fatigue resistance and failure mode.
Keywords: CAD/CAM; Endocrowns; Endodontic treatment; Fatigue failure; Lithium disilicate; Zirconia